Political Rights of Civil Servants in Indonesia - Hernadi Affandi (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2014)
AbstractThis paper highlights the regulation of political rights of civil servants (PNS) in Indonesia based on the 1945 Indonesian Constitution. Political rights are part of human rights that shall be guarded and protected by the State in the form of legislation ranging from constitution to its implementing regulations. The presence of regulation is substantial for safeguarding the existence and implementing political rights possessed by citizens, including civil servants. However, in practice there are restrictions by the lawmaker towards the political rights of the civil servants in Indonesia. In this regard, this paper attempts to highlight two issues: first, the position of civil servants in Indonesia in the 1945 Indonesian Constitution; second, the regulation of the political rights of civil servants in the implementing regulations of the 1945 Indonesian Constitution.Keywords: political rights, human rights, civil servants, 1945 Indonesian Constitution, implementing regulation. Pengaturan Hak Politik Pegawai Negeri Sipil di IndonesiaAbstrakTulisan ini menyoroti pengaturan hak Pegawai Negeri Sipil (PNS) di Indonesia berdasarkan Undang-Undang Dasar Negara Republik Indonesia tahun 1945 (UUD 1945). Hak politik merupakan bagian dari hak asasi manusia (HAM) yang harus dijaga dan dilindungi negara dalam bentuk pengaturan perundang-undangan mulai dari undang-undang dasar sampai dengan peraturan perundang-undangan pelaksananya. Kehadiran peraturan perundangundangan tersebut menjadi penting agar keberadaan maupun pelaksanaan hak politik yang dimiliki warga negara, termasuk PNS, dapat berjalan sebagaimana mestinya. Dalam praktiknya, terdapat pembatasan yang dilakukan oleh pembentuk undang-undang terhadap hak politik PNS di Indonesia. Berkaitan dengan hal tersebut, tulisan ini mencoba menyoroti dua persoalan: pertama, kedudukan PNS di Indonesia dalam UUD 1945; kedua, pengaturan hak politik PNS dalam peraturan perundang-undangan pelaksana UUD 1945.Kata Kunci: hak politik, hak asasi manusia, pegawai negeri sipil, UUD 1945, peraturan perundang-undangan. DOI: https://doi.org/10.22304/pjih.v1n3.a6